Characterization of chitosan-lysine surfactant bioactive coating on silicone substrate. (15th March 2020) - Ajdnik, Urban; Finšgar, Matjaž; Fras Zemljič, Lidija
Graphical abstract: Highlights: A new chitosan-anionic surfactant polyelectrolyte-surfactant complex was designed. Physical and mostly hydrophobic interactions drive the adsorption. Amoxicillin was efficiently loaded in the bioactive coating. Abstract: Chitosan (Chi) and anionic surfactant derived from lysine (77KS) were used to prepare a novel bioactive coating and as a drug delivery system for amoxicillin (AMOX) on a model polydimethylsiloxane (PDMS) surface. The bioactive coating was formulated as polyelectrolyte-surfactant complex (PESC). Aggregation behaviour between the cationic Chi and oppositely charged 77KS in bulk was analysed using turbidity and ζ -potential measurement. Furthermore, the adsorption and stability of the formulations were evaluated using quartz crystal microbalance with dissipation (QCM-D). The effect of the ionic strength and of the ultraviolet/ozone (UVO) activation of the PDMS films on the adsorption behaviour of the PESC complex was also examined. QCM-D monitoring showed stable adsorption of bare and AMOX-loaded complex on non-activated PDMS films, while the coating on UVO-activated PDMS samples desorbed after the rinsing step. Finally, X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry confirmed successful and homogenously distributed compounds.